Multi-Layer Oil- and Water-Resistant Food Containers Made Using Cellulose Nanofibril-Laminated Wood Veneer - Nabanita Das; Islam Hafez; Douglas Bousfield; Mehdi Tajvidi (Polysaccharides, 2025)
This work aimed at replacing per- or poly-fluoroalkyl substance (PFAS)-based food-serving containers with wood-based, oil- and grease-resistant food-serving containers. A novel container was developed by laminating wet cellulose nanofibril (CNF) films to both sides of yellow birch wood veneer using a food-grade polyamide–epichlorohydrin additive (PAE) as an adhesive. CNFs significantly improved the wood veneer container’s mechanical strength and barrier properties. The container’s mechanical testing results showed significant increases in flexural strength and modulus of elasticity (MOE) values in both parallel and perpendicular directions to the grain. All formulations of the container showed excellent oil and grease resistance properties by passing “kit” number 12 based on the TAPPI T 559 cm-12 standard. The water absorption tendency of the formulation treated at higher temperature, pressure, and longer press time showed similar performance to commercial paper plates containing PFASs. The developed composite demonstrates superior flexural strength and barrier properties, presenting a sustainable alternative to PFASs in food-serving containers. Both wood and CNFs stand out for their remarkable eco-friendliness, as they are biodegradable and naturally compostable. This unique characteristic not only helps minimize waste but also promotes a healthier environment. If scaled up, these novel containers may present a solution to the oil/grease resistance of bio-based food containers.